Regulation or deregulation: a reflection from the perspective of design thinking - Méndez Reátegui, Rubén (2020)
As a process and methodology, design thinking focuses on the actions of the user. It is a free and yet systematic process for creativity management, employing five innovation stages. Once applied, it transforms the «traditional practice» of generating ideas into thinking based on a deep understanding of user needs. This paper proposes design thinking as a methodological tool applicable to legal science,  riefly outlining the possibilities for its use in fields such as regulatory and deregulatory practice.